2023
DOI: 10.3390/jmse11010133
|View full text |Cite
|
Sign up to set email alerts
|

Design of Anti-Capsize Ship for Patrol Vessel with the Self-Righting Moment

Abstract: The patrol boat is one of the critical aspects for archipelago countries, such as Indonesia, to supervise and maintain the sea border. Due to rough sea conditions, the patrol boat could lose its stability due to the loss of a self-righting roll moment in severe waves. One of the most challenging aspects is to ensure the sufficient stability of the patrol boat during rough conditions. Another challenge is to design a boat that has a self-righting moment during rolling in extreme conditions. This paper examines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The self-righting moment is a concept where the ship can return to its upright position after being upside down to a certain degree or even completely upside down (180°) without the help of an external force. The previous study of a patrol boat with an effective self-righting moment was performed using experimental and numerical methods [1,2]. The results showed that the numerical method has the same phenomenon as the experiment: the ship has self-righting in all condition load cases.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…The self-righting moment is a concept where the ship can return to its upright position after being upside down to a certain degree or even completely upside down (180°) without the help of an external force. The previous study of a patrol boat with an effective self-righting moment was performed using experimental and numerical methods [1,2]. The results showed that the numerical method has the same phenomenon as the experiment: the ship has self-righting in all condition load cases.…”
Section: Introductionmentioning
confidence: 94%
“…The reference ship model based on MV Barracuda which was designed in previous studies [2]. For the main dimension of the ship can be seen in Table 1 and for the three dimension model shows in Figure 1.…”
Section: Ship Modelmentioning
confidence: 99%
“…Guan et al proposed a design method of self-righting decks, and they analyzed stability based on the combination of the particle swarm optimization and the sequential quadratic programming [18]. Trimulyono et al examined the design of an anti-capsize ship by improving the self-righting moment with different heights of deck house and designed a ship whose restoring arm is positive when the roll angle is between 0 • and 180 • [19]. With the improvement of algorithms and software, the efficiency of self-righting designs has greatly increased compared with traditional experiments.…”
Section: Introductionmentioning
confidence: 99%